Effects of L-carnitine supplementation in uremic patients receiving hemodialysis (尿毒症血液透析患者应用左卡尼汀临床效果观察) - YOU Huiqin (尤惠琴) (中西医结合护理)
Objective To investigate the effects of L-carnitine supplementation in uremic patients receiving hemodialysis. Methods Totally100 uremic patients undergoing hemodialysis were randomly divided into the control group and observation group according to the random number table, with 50 cases in each group. All patients received hemodialysis and routine nursing management, and patients in the observation group received intravenous drip of L-carnitine after hemodialysis treatment. The clinical effect of the hemodialysis treatment was evaluated, and changes of renal function indexes, nutrition indexes, serum inflammatory factors and complications were compared between two groups. Results The overall effective rate was 98. 00%(49/50)in the observation group and 86. 00%(43/50)in the control group, with no significant difference (P＞0. 05). Compared with patients in the controlgroup, patients in the observation group had a higher Ccr and lower level of Scr and BUN after treatment(P＜0. 05). The levels of PA, TRF, ALB and Hb in the observation group were higher than those in the control group after treatment(P＜0. 05). The levels of IL-6, CRP and TNF-α in the observation group were lower than those in the control group after treatment(P＜0. 05). There was no significant difference in incidence of complication between two groups(P＞0. 05). Conclusion The application of L-carnitine in hemodialysis treatment for uremic patients can improve the renal function and nutritional status, reduce the inflammatory reaction and complications, and helps to ensure the efficacy of hemodialysis treatment (目的 探讨左卡尼汀对尿毒症血液透析患者营养指标及炎症状态的影响。方法 选取2019年1月—2021年6月医院收治的尿毒症患者100例, 采用随机数字表法分为对照组和观察组, 各50例。两组均实施常规血液透析治疗和护理, 观察组于每次静脉透析治疗后静脉滴注左卡尼汀。评价两组治疗效果, 对比两组肾功能指标、营养指标、血清炎性因子指标、并发症发生情况。结果 观察组总有效率为98. 00%(49/50), 高于对照组的86. 00%(43/50), 差异无统计学意义(P＞0. 05)。治疗后, 观察组内生肌酐清除率(Ccr)高于对照组, 血肌酐(Scr)和尿素氮(BUN)水平低于对照组, 差异有统计学意义(P＜0. 05)。治疗后, 观察组前清蛋白(PA)、转铁蛋白(TRF)、白蛋白(ALB)、血红蛋白 (Hb)水平高于对照组, 差异有统计学意义(P＜0. 05)。治疗后, 观察组白细胞介素-6(IL-6)、C反应蛋白(CRP)和肿瘤坏死因子-α(TNF-α)水平低于对照组, 差异有统计学意义(P＜0. 05)。两组并发生发生率差异无统计学意义(P＞0. 05)。结论 尿毒症患者血液透析治疗中应用左卡尼汀, 能改善患者营养状况, 减轻炎症反应, 降低并发症风险, 确保透析治疗效果。)